General physical principle in dynamic model of reliability. (2017) - Prourzin, Vladimir A.
The general approach to the description of dynamic models of reliability is offered for variable loads. The approach is based on a general physical principle of reliability offered by us for dynamic systems. The dynamic system presents a change of vector of state variables of a system, depending on initial states and loads. The physical principle of reliability postulates existence of such set of state variables for which reliability of an engineering system at current time is determined only by current values of these variables and does not depend on their previous history. As consequence, the non-negative hazard of failure function is defined in the state system space. As a result, examination of reliability of an engineering system with variable loads is reduced to solution of ordinary differential equation system. Expressions for reliability indexes are obtained. Results of the work can have applications in the reliability, safety and risk theory, in accelerated tests, in the area of fatigue damage accumulations at variable loads, in diagnostics, in medicine.